Reflets du pouvoir et de la société dans les Caractères de La Bruyère - Zsák, Helga (Verbum – Analecta Neolatina, 2015)
Among French 17th-century moralists, La Bruyère seems to be the only one who had a political and social conception described in the many chapters of Caractères. Inspired perhaps by antic philosophers and by his contemporary political theoreticians, he is courageous enough to advise the king and to underline his duties and his service toward the subordinates. His realistic portraits and descriptions and his philanthropic views announce, after the century of the birth of the State of law in France, the century of Enlightenment.